Conceptual Framework for Immunization of Phiman Primary Care Unit - หิมมา อภิชญา; เชยบัวแก้ว วัลลภา (Journal of Health Science of Thailand, 2024)
Immunization through vaccination to prevent disease is necessary and very important to reduce morbidity and mortality in children. Children’s illnesses not only affect the children themselves and their family, but also the society and the nation as well. This study aimed to develop a conceptual framework for immunization in order to reduce morbidity and death rates among children in Phiman primary care unit of Satun Hospital, Stun Province, Thailand. A concept was developed from a review of relevant literature and models by integrating three standards in immunization work which included: (1) vaccine management standards and cold chain systems, (2) quality standards for vaccination services, and (3) standards for recording information in the immunization work; together with the application of systems theory including inputs, processes, and results, in the context of the Phiman primary care unit. The study was conducted during December 2020 to May 2021. There were 490 samples of children guardians, health care volunteers, teachers of child development centers, Islamic leaders and Phiman PCU staff. The results of the study after the implementation of the conceptual framework revealed that the knowledge, attitude, awareness of vaccination and satisfaction with immunization services for newborns were all in creased, particularly the knowledge and attitude which were significantly improved (p<0.01). Thus, the framework should be wider utilyzed in order to properly manage child vaccination program which will eventually protect children from vaccine preventable diseases. In addition, the framework can become a component for developing policies related to the management of immunization clinics